Chief for Life: Harold Breier and His Era - (:unkn) unknown (My University, 2002)
Harold Breier served as Milwaukee's Chief of Police from 1964 until 1984. His tenure occurred during a time of cultural upheaval in the United States, marked by the turmoil of the civil rights movement, the peace movement, and a youth rebellion against traditional societal values and norms. Many people perceived Breier as an opponent of cultural or political change. He was accused of tolerating excessive police force, especially when minority citizens or counterculture youth were involved, and presiding over a racially segregated police department. Others credited him with making Milwaukee one of the safest cities in the country and protecting the core values of American society. Chief Breier's authority was unique among urban police chiefs. He enjoyed statutory lifetime tenure and had exclusive power to make and enforce departmental rules. Although most of his formal power was derived from state law, much of his influence resulted from the general perception that he commanded a large following among the electorate, and any public official opposing his policies or methods would be punished by the voters. Acting on that perception, most local and state politicians refrained from criticizing him or challenging his virtually unlimited power over law enforcement in Milwaukee. Mayor Henry Maier occasionally worked around Breier but denied that he was doing so. A series of events involving Breier and his department alienated segments of the community and resulted in efforts to curb the chiefs formal power. The result was a change in state law, which removed much of his unilateral authority. His inability to influence those changes, and the electoral success of some of his opponents, raised questions about his political power. Breier retired rather than serve with diminished authority. Although Breier's tenure arrangement was unique, his career helps explain the cultural milieu in which other urban police chiefs of his era operated. It sheds light on the historic political role of urban police chiefs and their influence on the development of public policy.
Keywords: Social sciences; Language; literature and linguistics; Harold Brier; Police chiefs; Urban law enforcement; Wisconsin